The influence of perceived ease of use, perceive usefulness, and trust on customer’s intention to use "Bebas Bayar" mobile payment application in Indonesia - Sanaji, Sanaji; Indarwati, Tias Andarini; Candra, Ika Diyah (Technium Social Sciences Journal, 2021)
The presence of a mobile payment application has changed the way people to do a financial transaction. It enables people to send, process and receive money at anywhere and anytime. "Bebas Bayar" is one of the most downloaded mobile-based apps in Indonesia that support the payment for the electricity bill, telephone, and all financial transaction which connected with user’s banking account. Therefore, this study aims to analyze the influence of customer perceived value of this app to its customer’s purchase decision based on Technology Acceptance Model 2 (TAM 2). The research method is Multiple Regression that tested the influence of perceived ease of use, perceived usefulness and trust to customer’s intention to use ‘Bebas Bayar’ service. The study result is the customer perceived usefulness, and customer trust are significantly influenced the customer’s intention to use, whereas customer’s perceived ease of use does not significantly influence the customer’s intention to use. This study is expected to give managerial implication about how to improve the app developer’s service and product development based on the customer’s perceived value and customer’s intention to use. The research about consumer adoption to mobile payment application that measured by Technology Acceptance Model (TAM 1) were frequently done. Nevertheless, there is less research on how to measure the influence of customers perceived values on their intention based on the latest development of TAM 2. Besides, there is still no research about the relationship of TAM 2 variables to customer’s intention to use.